Calibration of soil P methods and common bean response to phosphate fertilizer row application - de Miranda, Leo Nobre; de Azevedo, Juscelino Antonio; de Miranda, Jeanne Christine Claessen; Gomes, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2002)
The common bean and maize have presented significative responses to phosphate fertilizer, but it is necessary to evaluate the soil P availability to recommend P fertilization. The objective of this work was the calibration of Mehlich-1, Mehlich-3 and Ion-exchange Resin methods, through the relations between soil P availability and the crops grain yield, as well as the evaluation of the response of common bean to P row application. The treatments consisted of 250, 500 and 1.000 kg ha-1 P2O5 broadcasting, cultivating four crops of common bean ’Carioca’ in rotation with maize ’BR 201’. For the last common bean crop, the splitted plots received 0, 75, 150 and 300 kg ha-1 P2O5 in row. The grain yield increased with phosphate levels, being linear for common bean up to 1.000 kg ha-1 P2O5, and quadratic for maize. The three methods presented a good capacity to predict the soil P availability, with significative correlation among themselves. The soil P critical level to obtain 80% of maximum grain yield for corn was 10, 14 and 17 mg dm-3, respectively for Mehlich-1, Mehlich-3 and Resin methods. The common bean presented a significative response to phosphate fertilizer in row, which magnitude depended on the previous soil P availability.